(3GdahGFO GdVjGFjIs - (3fhQ GdOjf YHO GdQMef Hf CMeO Hf eMeO GdLGej GdfbTHfOj, GdLGej,J (B898 (3g` s; (3GHf GdMGLH , LeGd GdOjf CHh YeQh GHf GdMGLH, LeGd GdOjf CHh YeQh GHf GdMGLH,J (B646 (3g` s ((3YHO GdQMef GdLGei s)
(3ChdgG (B:s
(3GdMeO dhdjg hGdUdGI Ydi fHjg hYdi Bdg hCUMGHg CeG HYO agPg ahGFO hGajI dMd eTcdGJ GdcGajI s
(3BNQgG (B:s
(3hEPG GfVe cbhdc ai GVQHf GVQHkG JTHjgG dgG HGdJfhjf EPG GfaJM eG bHdgG JbdH CdakG hEPG GfVe Ch GfcSQ JMPa Je s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B211 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B6 - (3U (B265s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1372s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdfMhs